Histone chaperone activity of Fanconi anemia proteins, FANCD2 and FANCI, is required for DNA crosslink repair - Sato, Koichi; Ishiai, Masamichi; Toda, Kazue; Furukoshi, Satoshi; Osakabe, Akihisa; Tachiwana, Hiroaki; Takizawa, Yoshimasa; Kagawa, Wataru; Kitao, Hiroyuki; Dohmae, Naoshi; Obuse, Chikashi; Kimura, Hiroshi; et al. (The EMBO journal, 2012)
Fanconi anaemia (FA) is a rare hereditary disorder characterized by genomic instability and cancer susceptibility. A key FA protein, FANCD2, is targeted to chromatin with its partner, FANCI, and plays a critical role in DNA crosslink repair. However, the molecular function of chromatin‐bound FANCD2‐FANCI is still poorly understood. In the present study, we found that FANCD2 possesses nucleosome‐assembly activity in vitro . The mobility of histone H3 was reduced in FANCD2‐knockdown cells following treatment with an interstrand DNA crosslinker, mitomycin C. Furthermore, cells harbouring FANCD2 mutations that were defective in nucleosome assembly displayed impaired survival upon cisplatin treatment. Although FANCI by itself lacked nucleosome‐assembly activity, it significantly stimulated FANCD2‐mediated nucleosome assembly. These observations suggest that FANCD2‐FANCI may regulate chromatin dynamics during DNA repair. Unexpected nucleosome remodelling activities of FANCD2‐FANCI proteins offer new clues as to their essential yet still enigmatic functions in DNA interstrand crosslink repair.